ANALISIS FAKTOR-FAKTOR TERHADAP PERUBAHAN HARGA SAHAM DENGAN KEBIJAKAN DEVIDEN SEBAGAI VARIABEL INTERVENING PADA SEKTOR FARMASI YANG TERDAFTAR DI BEI TAHUN 2018-2022 - Salsabila, Nindya; Wahyuni, Ika; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
This research purposed to find out the factors of changes in stock prices with dividend policy as an intervening variable in the pharmaceutical sector listed on Indonesia Stock Exchange in 2018-2022. The sampling technique used in this study was purposive sampling. Data analysis and hypothesis testing in this study applied Partial Least Square Structural Equation Modeling The results of direct effect hypothesis test using Smart PLS 3.0 application showed that current ratio has a significant positive effect on dividend policy, ROA has a significant positive effect on dividend policy,DER has a significant negative effect on dividend policy,current ratio has an insignificant negative effect on stock prices, ROA has an insignificant positive effect on stock prices, DER has insignificant positive effect on stock prices, dividend policy has a significant positive effect on stock prices, current ratio has a significant positive effect on stock prices through dividend policy, ROA has a significant positive effect on stock prices through dividend policy, DER has a significant negative effect on share price through dividend policy.